Integrated Lean Service - Digital Marketing Model to Increase the Profitability of Debit Cards in Retail Banking - Garcia Marreros, Franco Jesus (2023)
In the financial sector, the banking industry is one of the most important due to the large number of economic resources it handles, as well as the amount of employment it generates. For this reason, the correct functioning of the processes within the said industry is key. Being the debit card one of the main products of the banks, high performance of it is expected. However, many debit cards are not used and represent a large percentage of the financial losses of banking entities. Given this, to solve this problem, an integrated model based on lean service and digital marketing is proposed, using tools such as VSM, poka-yoke, work standardization and costumer-centered marketing. The proposed model was validated through a simulation in Arena, where the consumer behavior and the lean model in the process shows an improvement of 2.7% in cost-effectiveness. On the other hand, using surveys, customer-focused marketing strategies that would enhance the use of debit cards were determined)